Startups and innovation challenges : does the use of social media impact the new product development process in Startups? - Silva, Diogo Miguel Ervilha da (2023)
This thesis investigates the impact of social media usage on the new product development process in Portuguese startups. The study aims to fill the gap in research on how social media usage impacts the different stages of the new product development process in startups. The research objectives are twofold: to assess the innovation intentions of Portuguese startups over the next 12 months and understand the extent to which they plan to engage in new product development, and to investigate the impact of social media usage on the new product development process in these startups. The study employs a quantitative research design, collecting data from a sample of 76 Portuguese startups using a self-administered survey. The results indicate that external knowledge acquisition is more prevalent than internal knowledge generation, and startups in Portugal are increasingly using social media as a tool for product development. The findings also suggest that social media usage is an important factor that can positively impact the level of innovation in a company. Overall, the study provides valuable insights into how startups can use social media effectively to develop and launch new products and contributes to a better understanding of the role of social media in the Portuguese startup ecosystem. The recommendations provided can inform startup managers, policymakers, and researchers and serve as a foundation for further research in this field.